Beyond the Code: Recovering Iḥsān as the Antidote to Modern Islamic Legalism - Muhammad Imran Saleem Channar (SUHU: Journal of Sufism and Humanities, 2025)
This study examines the crisis of legalism in contemporary Islamic thought, characterized by an overemphasis on outward legal compliance (Sharīʿah) at the expense of inward spiritual cultivation (Tazkiyah) and moral excellence (Iḥsān). The research employs a qualitative analytical methodology combining textual hermeneutics of classical Islamic sources with historical analysis of colonial and postcolonial transformations, supplemented by contemporary sociological data from Muslim communities globally. Primary sources include Qur'anic exegesis, Prophetic traditions, and spiritual treatises by al-Ghazālī, Ibn al-Qayyim, and Ibn al-ʿArabī, while secondary sources encompass colonial archives and contemporary ethnographic studies. Findings reveal that modern legalism represents an unprecedented epistemological rupture caused by colonial codification, nation-state formation, and identity politics, which severed law from its spiritual-ethical framework. The systematic marginalization of classical sciences of the heart (ʿUlūm al-Qulūb) has produced psychological pathologies including religious scrupulosity, social fragmentation, and ethical minimalism. The study identifies iḥsān—worshipping God as though seeing Him—as the essential corrective that historically integrated external compliance with internal transformation. The research concludes that healing this dichotomy requires comprehensive pedagogical reform integrating spiritual texts into curricula, establishing urban spiritual centers, developing contemporary spiritual literature addressing modern challenges, and fostering grassroots community initiatives, thereby restoring Islam's holistic vision where law serves as a vehicle for spiritual realization rather than an end in itself.